Case report: Long term response to growth hormone in a child with Silver-Russell syndrome-like phenotype due to a novel paternally inherited IGF2 variant - Ventresca, Silvia; Lepri, Francesca Romana; Criscuolo, Sabrina; Bottaro, Giorgia; Novelli, Antonio; Loche, Sandro; Cappa, Marco (Frontiers in Endocrinology, 2024)
Silver-Russell syndrome (SRS, OMIM 180860) is a rare genetic disorder with a wide spectrum of symptoms. The most common features are intrauterine growth retardation (IUGR), poor postnatal development, macrocephaly, triangular face, prominent forehead, body asymmetry, and feeding problems. The diagnosis of SRS is based on a combination of clinical features. Up to 60% of SRS patients have chromosome 7 or 11 abnormalities, and <1% show abnormalities in IGF2 signalling pathway genes (IGF2, HMGA2, PLAG1 and CDKN1C). The underlying genetic cause remains unknown in about 40% of cases (idiopathic SRS). We report a novel IGF2 variant c. [-6-2A>G] (NM_000612) in a child with severe IUGR and clinical features of SRS and confirm the utility of targeted exome sequencing in patients with negative results to common genetic analyses. In addition, we report that long-term growth hormone treatment improves height SDS in this patient.